HUBUNGAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KARYAWAN DI UPTD PUSKESMAS SIAK HULU II KECAMATAN SIAK HULU KABUPATEN KAMPAR TAHUN 2018 - reno renaldi; Hastuti Marlina; Nila Puspita Sari (STIKes Al-Insyirah Pekanbaru, 2019)
Leadership is an activity to influence the behavior the other people, that is individuals and groups towards achievement the goal in leadership activities, it is necessary to think about leadership style, leadership style is a behavior norm which is used by someone when the person tries to influence the behavior of the others people. During his leadership there were still employees who complained about what was he done as the head of Health Center such as still be there of task which conducted by officers who were not in accordance with the field of competence they had and also there were still employees who arrived not on time and go back home early. This research purpose is to knowing the coorrelation of directive leadership, supportive, achievement, and participatory styles toward employees motivation in Siak Hulu II Health Center. This research method is a quantitative research with cross sectional design. This research was conducted in Siak Hulu II Health Center in July. The population of this research were all employees in Health Center with total of 63 respondents and using total sampling techniques. Data collecting are using questionnaire. Data analysis is using univariate and bivariate analysis and chi-squere test with a 95% confidence level. This research results indicate there is correlation among directive leadership style (p value = <0.001), supportive (p value = 0.001), achievement (p value = 0.047) and participative (p value = <0.001) toward motivation of employees in Siak Hulu Health Center II. So it can be concluded that all leadership style variables are related to employee motivation in Siak Hulu Health Center II. It is suggested to the head of Health Center to impose sanctions on employees who arrive late and give awards to employees who have the ability to do a job in accordance with procedures and schedules.